2023
DOI: 10.1302/2046-3758.127.bjr-2022-0420.r1
|View full text |Cite
|
Sign up to set email alerts
|

The association between selenium and bone health: a meta-analysis

Abstract: AimsPrevious studies have suggested that selenium as a trace element is involved in bone health, but findings related to the specific effect of selenium on bone health remain inconclusive. Thus, we performed a meta-analysis by including all the relevant studies to elucidate the association between selenium status (dietary intake or serum selenium) and bone health indicators (bone mineral density (BMD), osteoporosis (OP), or fracture).MethodsPubMed, Embase, and Cochrane Library were systematically searched to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Similarly, Walsh et al found that Se intake has no significant impact on bone improvement in postmenopausal women [54]. In contrast, Xie et al, reported that Se supplementation enhanced BMD and reduced the risk of OP [55], and a study by Park et al found that low BMD was associated with decreased hair Se levels [56]. However, Xue et al found that moderate Se intake increased BMD, whereas excessive intake reduced BMD [57].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Walsh et al found that Se intake has no significant impact on bone improvement in postmenopausal women [54]. In contrast, Xie et al, reported that Se supplementation enhanced BMD and reduced the risk of OP [55], and a study by Park et al found that low BMD was associated with decreased hair Se levels [56]. However, Xue et al found that moderate Se intake increased BMD, whereas excessive intake reduced BMD [57].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of bone remodelling disorders in KBD patients is attributed to an imbalance between osteoblast-mediated bone formation and osteoclast-mediated bone resorption (74). The relationships between Se and the bone turnover rate and bone mineral density have been established by various studies (75)(76)(77). Inadequate Se levels can impede growth and alter bone metabolism, decreasing the bone turnover rate and bone mineral density (78).…”
Section: Impact Of Se On the Pathogenesis Of Kbdmentioning
confidence: 99%
“…Furthermore, studies have suggested that selenium supplementation may enhance the bone mineral density and improve bone quality, thereby facilitating bone regeneration and fracture healing [7]. Despite these advancements, there remains a dearth of literature on the production of selenium-incorporated bioactive glass.…”
Section: Introductionmentioning
confidence: 99%